Inclusive Basic Education in South Africa: Issues in its Conceptualisation and Implementation - Lucyline Nkatha Murungi (Potchefstroom Electronic Law Journal, 2015)
Education is one of the most topical issues in South Africa. In recent years, particularly in the period after the adoption of the UN Convention on the Rights of Persons with Disabilities (2006) (hereinafter CRPD), the discourse on the education of children with disabilities has mainly focused on the potential of White Paper 6 on Special Needs Education (2001) (hereinafter WP 6) and its implementing programmes to facilitate the realisation of the right to education for children with disabilities. The CRPD proposes inclusive education as the appropriate way of ensuring the right to education for children with disabilities, and sets out a framework for the implementation thereof. In addition, the CRPD sets out other principles which essentially redefine the approach to the interpretation and implementation of the rights of persons with disabilities. One such principle is the principle of non-discrimination, which demands that all rights be implemented on a basis of equality between all people, disability notwithstanding.